The investigation of the optical spectra in process of magnetron deposition - Demchishin, A.V.; Evsyukov, A.N.; Goncharov, A.A.; Kostin, E.G. (Вопросы атомной науки и техники, 2008)
We describe the state-of-the-art method of monitoring optical parameters the cylindrical gas discharge plasma of magnetron type. An analysis and characterization of the spectrum during a process of titanium nitride deposition is carried out. The optimum conditions of titanium nitride synthesis on substrates are determined. A characterization of deposited TiN films is made. Запропонований новий метод контролю оптичних параметрів плазми циліндричного газового розряду магнетронного типу в дійсному масштабі часу. Проведений аналіз та характеризація спектру в процесі напилення нітриду титана. Знайдені оптимальні умови отримання плівок нітриду титана. Виконано їх рентгенофазовий аналіз та виміряна мікротвердість. Предложен новый метод контроля оптических параметров плазмы цилиндрического газового разряда магнетронного типа в реальном масштабе времени. Проведен анализ и характеризация спектра в процессе напыления нитрида титана. Найдены оптимальные условия получения пленок нитрида титана. Выполнен их рентгенофазовый анализ и измерена микротвердость.